Mineral-facilitated aqueous synthesis of hydrogen cyanide from prebiotically abundant amino acids for chemical evolution - Zening Yang; Yamei Li; Norio Kitadai; Masahiro Yamamoto; Yuichiro Ueno; Yanjing Lu; Ailong Li; Kiyohiro Adachi; Akira Yamaguchi; Daisuke Hashizume; Ryuhei Nakamura (Proceedings of the National Academy of Sciences, 2026)
Recent advances in prebiotic chemistry suggest that hydrogen cyanide (HCN) serves as a fundamental precursor for nearly all essential biomolecules and protometabolic processes for life’s emergence. Although prevailing models of endogenous cyanide production rely on atmospheric methane, the availability of methane remains uncertain. Unlike methane, amino acids were likely prebiotically abundant, forming through multiple synthetic pathways under a methane-free, nonreducing atmosphere. Here, we demonstrate that HCN can form from proteinogenic amino acids in anaerobic aqueous solutions facilitated by geochemically available minerals, offering a route to overcome HCN scarcity under a nonreducing atmosphere. On manganese dioxide, the glycine-to-cyanide conversion proceeded across a broad range of pHs (2.0 to 12.6) and substrate concentrations (1 μM to 100 mM), achieving a maximum selectivity of 57%. The reaction involves α-proton abstraction in amino acids, which is distinct from conventional chemical decarboxylation processes of amino acids, highlighting the unique role of MnO 2 in activating the α-C-H bond to form HCN. HCN generation was observed for nearly all proteinogenic amino acids and short peptides. Because amino acids can be synthesized from HCN-independent pathways from abundant carbon sources such as CO 2 and CO, amino acid-derived HCN alleviates the requirement on atmospheric methane and can sustain continued chemical evolution in ambient aqueous environments.